Effect of Metacognitive Instructional Strategy on Chemistry Students’ Academic Achievement and Retention - Juliana Nkiru Nnoli; Adaobi Oluchukwu Ibeh (International Journal of Administration and Education (IJAE), 2025)
The study, effect of Metacognitive Instructional Strategy (MIS) on Chemistry student academic achievement and retention in secondary schools in Orumba North Local Government Area, was conducted in response to the increasing declining interest in chemistry, lack of technological advancement, creativity and abstract nature of chemistry content among chemistry students. The study was guided by six research questions and six null hypotheses.  Quasi-experimental research design, which involves comparing groups to determine the effect of an intervention, was adopted for the study. The population of the study was 234 senior secondary year two (SS2) students who offered Chemistry in Orumba North Local Government Area in Anambra State, Nigeria in the year 2024/2025. A sample size of 129 students was drawn from the population using simple random sampling (balloting with replacement). The instrument for data collection was Periodic Table Achievement Test (PTAT) validated by three experts, two from the department of science and one department of educational foundation, all from the faculty of education. The reliability of the instrument was established using Kuder-Richardson 20 for PTAT which yielded coefficient values of 0.82. Data  generated was analyzed using Mean and standard deviation to answer the research questions, while ANCOVA was used to test the null hypotheses at 0.05 significant levels The findings of the study revealed that students taught with Metacognitive instructional strategy achieved higher mean scores in Chemistry concepts, than those taught with conventional lecture method. It also revealed that male students taught Chemistry using MIS had higher mean academic achievement scores than females. The study found a significant interaction effect between instructional strategy and gender on academic achievement and retention. The study recommended among others that Chemistry teachers should adopt Metacognitive instructional strategy in teaching Chemistry to enhance academic achievement and retention and apply gender-responsive strategy when using MIS to ensure male and female students are equally engaged during Chemistry instruction.